Climate Change and Rising Temperatures - Kurtz, Kevin (Minneapolis, MN : Lerner Publications, 2019)
"Learn how climate change impacts the temperatures here on Earth in this engaging and informative read."-- Provided by publisher.
What is climate change -- Hotter all the time -- Temperature and our planet -- Scientists respond.
Includes bibliographical references and index.
Ages 8-11.
Keywords: Climatic changes -- Juvenile literature; Global warming -- Juvenile literature; Global environmental change -- Juvenile literature; Nature -- Effect of human beings on -- Juvenile literature